Question about SoftMath Algebrator - Algebra Homework Solver (689076614429)

X+2y 0ver 9+5y

Ad

(9-5+(7-2).4)=24

Posted on Sep 07, 2012

Ad

Hi bem4u2

If the question was like this: x+2y/9+5y then the order of operations would apply because it is a string of operations

But your question is the equivalent of a single fraction

In this case,

Take the numerator alone apply the order of operation

Take the denominator and apply the order of operations

Then it becomes a single fraction

Hope this answer your question

Have a good day

luciana44

Posted on Nov 03, 2009

Ad

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)

click here to download the app (for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

y = x+1

y = (4) + 1

y = 5

y = x + 1

y = (-4) + 1

y = -3

2y - 2 = 2x

2y - 2 = 2 (4)

2y - 2 = 8

2y - 2 + 2 = 8 + 2

2y = 10

2y/2 = 10/2

y = 5

2y - 2 = 2(-4)

2y - 2 = -8

2y -2 + 2 = -8 + 2

2y = -6

2y / 2 = -6 /2

y = -3

The results are the same, implying that they are the same line.

Why?

2y - 2 = 2x

2y - 2 + 2 = 2x + 2

2y = 2x + 2

divide everything by 2

y = x + 1

Good luck,

Paul

y = (4) + 1

y = 5

y = x + 1

y = (-4) + 1

y = -3

2y - 2 = 2x

2y - 2 = 2 (4)

2y - 2 = 8

2y - 2 + 2 = 8 + 2

2y = 10

2y/2 = 10/2

y = 5

2y - 2 = 2(-4)

2y - 2 = -8

2y -2 + 2 = -8 + 2

2y = -6

2y / 2 = -6 /2

y = -3

The results are the same, implying that they are the same line.

Why?

2y - 2 = 2x

2y - 2 + 2 = 2x + 2

2y = 2x + 2

divide everything by 2

y = x + 1

Good luck,

Paul

Feb 07, 2017 | The Office Equipment & Supplies

Possibly an engine timing issue

Dec 12, 2014 | 2001 Ford Explorer

Both should work.

16x - 2y = 16

4x - 2y = -8

-----------------

12x = 24

x = 2

y = 8

2y=4x + 8

y = 2x + 4

16x - 2(2x + 4) = 16

16x - 4x -8 = 16

12x = 24

x = 2

y = 8

Good luck.

Paul

16x - 2y = 16

4x - 2y = -8

-----------------

12x = 24

x = 2

y = 8

2y=4x + 8

y = 2x + 4

16x - 2(2x + 4) = 16

16x - 4x -8 = 16

12x = 24

x = 2

y = 8

Good luck.

Paul

Oct 05, 2014 | Office Equipment & Supplies

dy/dx = e^(3x + 2y) = (e^3x)(e^2y)

INT e^-2y dy = INT e^3x dx

Can you finish it from there? Don't forget constant of integration.

I hope this helps!

INT e^-2y dy = INT e^3x dx

Can you finish it from there? Don't forget constant of integration.

I hope this helps!

May 06, 2011 | Computers & Internet

If you mean this to be a logic statement, it will always be false (0). You might be getting an error because you need parentheses around the whole thing.

If you mean the 2y=2 to be 2y 2 then y=2

If you mean the 2y=2 to be 2y-2 then y=4

You should give more info on your problem next time.

If you mean the 2y=2 to be 2y 2 then y=2

If you mean the 2y=2 to be 2y-2 then y=4

You should give more info on your problem next time.

Apr 30, 2011 | Texas Instruments TI-83 Plus Calculator

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

2y - x = 3

x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is**x = 1**, **y = 2**

or in ordered pair notation**(1, 2)**

x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is

or in ordered pair notation

Jun 29, 2009 | Computers & Internet

4x+8y=20 || /4

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

Mar 10, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

Hi joanmae jmeh;

You can add these equations just like you would numbers

3x + 2y = 7

5x - 2y = 1

-----------------------

8x =8

x=1

Now plug x = 1 back into either equation and you can solve for y

Y = 2

When you add the 2 equations together the +2y and the -2y cancel

out

Hope this helps Loringh Please leave a rating for me Thks

You can add these equations just like you would numbers

3x + 2y = 7

5x - 2y = 1

-----------------------

8x =8

x=1

Now plug x = 1 back into either equation and you can solve for y

Y = 2

When you add the 2 equations together the +2y and the -2y cancel

out

Hope this helps Loringh Please leave a rating for me Thks

Dec 01, 2008 | Bagatrix Algebra Solved! 2005 (105101) for...

126 people viewed this question

Usually answered in minutes!

×